Enhancing the Routing Security through Node Trustworthiness using Secure Trust Based Approach in Mobile Ad Hoc Networks - M. Venkata Krishna Reddy; P.V.S. Srinivas; M. Chandra Mohan (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Mobile Ad Hoc Networks, also known as MANETs are the part of networks which utilizes the technologies like Internet of Things. Internet is filled with known as well as unknown sources which are still considered as a challenge. Considering the security challenges in the topology, infrastructure and bandwidth of these networks the below secure trust approach is proposed. Among all the existing and proposed approaches to provide the security to these networks seemed lengthy and complex. The study here focuses on the trust factor of the nodes to simulate the challenge of providing the secure transmission. The challenge is approached through calculations from the simulations based on node distribution and its trustworthiness. In order to evaluate the performance of the proposed secure trust mechanism, three scenarios are considered here. Routing between source ad destination without any trust calculation, routing with only direct trust factor and routing with proposed secure trust calculation from the node’s distributions. The goal of proposed method in this paper is about the secure routing for transmission by simulating the important factor Node trustworthiness using new trust mechanism proposed i.e. secure trust. The metrics from the simulations shows the efficient performance of the proposed method.